QUALITY SERVICE MANAGEMENT AND CUSTOMER SATISFACTION IN SELECTED SERVICE INDUSTRIES IN THE PROVINCE OF CAPIZ - AquiÃ±o, Ronelyn Baes (President University, 2025)
The study investigated the level of quality service management and the degree of customer satisfaction of selected service industries in the Province of Capiz. The service industry in this study is limited to the three resort hotel that were willing to participate in this study, also limited to the quality service management in terms of product and service while customer satisfaction in terms of quality service, empathy, and cost. The study used the descriptive-correlational research design. Data were gathered from 105 local and foreign guests of three selected resort hotels. The precise number of guests per day in the service industry was considered classified data by management. Therefore, quota sampling was used for the study. A researcher-made, validated and reliability tested questionnaire was utilized to gather needed data. Frequency count, percentage, mean, t-test, f-test, ANOVA and Pearson r were the statistical tools used to analyze and interpret the gathered data. The results of the study revealed that the level of quality service management and the degree of customer satisfaction, when respondents were grouped according to reason of stay, type of guest, and nationality of guest, were very satisfactory. There was no significant difference in the level of quality service management and degree of customer satisfaction of selected service industries in the Province of Capiz when respondents were grouped according to reason of stay, type of guest, and nationality of guest. The level of quality service management and the degree of customer satisfaction of selected service industries in the province of Capiz were significantly related.